Human sacrifice in witchcraft ritual: a need for the anti witchcraft law - Mahyuddin, Ismail; Jahid, Sidek; Nurkarimah, Yusof (Universiti Sains Islam Malaysia (USIM), 2021)
Witchcraft or black magic is among the ancient mystical ritual in the world. It involves the engagement of jinn and demons with specific purposes. Based on literature, there were cases of human sacrifice in witchcraft ritual. This study specifically seeks to explore the rituals of demonic worship and human sacrifice in witchcraft. This study applies library research particularly by analyzing history and legal background of the issue. In some court cases, it was proven that these practices of detestable witchcraft require certain organs of a human body, especially of a child, to be one of the devil's objects of worship. This study will also discuss illustration (a) of the section 364 of the Penal Code which specifically mentioned about crime of kidnapping or abducting any person to be murdered and presented to idolatry. The results of this study justify a proactive action need to be taken by the authorities specifically by enacting the law to fight against witchcraft.